Collins COBUILD key words for IELTS - Moore, Julie (HarperCollins Publishers, 2011)
Collins Easy Learning Key Words for IELTS series is a brand-new range of three graded books which contain the essential vocabulary students need to succeed in the IELTS exam. These books have been specially created for foreign learners of English who plan to take the IELTS exam to demonstrate that they have the required ability to communicate effectively in English, either at work or at university